Traditional Chinese Medicine retention enema and nursing interventions on constipation symptoms in a patient with severe pneumonia (中药保留灌肠治疗1例重症肺炎患者便秘的护理体会) - WANG Ye (王烨); WANG Liangmin (王梁敏); E Haiyan (鄂海燕); SHENG Yana (盛娅娜); SHI Mingjie (石明杰); BAI Mei (白梅) (Journal of International Translational Medicine Limited, 2023)
This paper summarized the practice of Traditional Chinese Medicine retention enema and nursing interventions on constipation symptoms in a patient with severe pneumonia. The nurses had carried out a comprehensive assessment on patient's condition. Based on conventional interventions such as anti-infective therapy, enteral nutritional support, psychological care, Traditional Chinese Medicine retention enema by syndrome differentiation was conducted to improve the recovery of gastrointestinal function and relieve the constipation symptoms of the patient. (本文总结中药保留灌肠治疗1例重症肺炎患者便秘的护理经验。护理人员科学评估, 基于中医辨证, 在抗感染治疗、肠内营养支持、心理护理等常规治疗和护理的基础上, 开展中药保留灌肠干预, 在促进患者胃肠功能恢复的同时, 兼顾补中益气, 有效缓解患者便秘症状, 促进早期康复。)